Education Revolution in Indonesia:Historical Footprints and Future Direction - Yuangga, Kharisma Danang (Universitas Negeri Makassar, 2025)
The landscape of education in Indonesia has undergone significant transformations, mirroring the nation's dynamic socio-political evolution and its aspirations for growth and development. Historically, Indonesian education has been shaped by a plethora of influences, ranging from its colonial past to the influence of global educational trends, reflecting a journey from traditional to modern pedagogical approaches. In the contemporary context, there is a discernible shift towards integrating technology and adopting progressive teaching methodologies to enhance learning outcomes and ensure educational equity. This transition is emblematic of Indonesia's broader efforts to harmonize its rich cultural heritage with the imperatives of a globalized world, thereby fostering a learning environment that is both locally resonant and globally relevant. Qualitative research in this domain offers nuanced insights into these transformations, capturing the complex interplay between policy shifts, pedagogical innovations, and societal expectations. By examining educational practices, curricular changes, and stakeholder perceptions, this research sheds light on the evolving educational paradigms in Indonesia, highlighting the factors driving change and the challenges encountered. Through this lens, the study contributes to a deeper understanding of Indonesia's educational landscape, providing a foundation for future initiatives aimed at nurturing a well-informed, skilled, and adaptable citizenry.